Basic Principles of Innovation Management in the Urban Economy of Smart-City - Ilyinichna Romanova, Anna; Sergeevich Romanov, Dmitrii; Viktorovna Maksimchuk, Olga; Vladimirovich Voronin, Alexander (International Journal of Engineering and Technology, 2018)
The key direction in the formation of a "smart" city is its spatial development. The principles of accessibility, openness and comfort of the urban space that creates conditions for the interaction of its inhabitants come in place of the principles of industrial, technocratic minimalism. Hence, the task of municipalities to form fundamentally new public spaces. Flexible and multifaceted. The urban economy is often identified with housing and communal services, thereby emphasizing the priority for local authorities to provide people with heat, water, electricity in front of other issues. This most important sphere, complicated by a multitude of problems, is a grateful field for innovation and application of a special economic toolkit. And it is here that there is a possibility of a qualitative innovation breakthrough, in terms of creating and developing an "intelligent" urban economy, or SMART-city.Â Â Â